Burial in the western Central Andes through Oligocene to Miocene ignimbrite flare-ups recorded by low-temperature thermochronology in the Cañete Canyon, Peru - Audin, Laurence (2023)
Thermochronological data are essential to constrain thermal and exhumation histories in active mountain ranges. In the Central Andes, bedrock outcrops are rare, being blanketed by widespread late Palaeogene–Neogene and younger volcanic formations. For this reason, the exhumation history of the Western Cordillera (WC) in the Peruvian Andes has only been investigated locally along the mountain range. Dense thermochronological data are only available in canyons of the Arequipa (16° S) and Cordillera Negra regions (10° S). We present new apatite (U-Th)/He and fission-track data from the 1 km deep Cañete Canyon (13° S), where the Oligo-Miocene deposits are preserved lying conformably on an Eocene palaeo-topographic surface. Thermal modelling of thermochronological data indicate that the 30–20 Ma ignimbrite deposits overlying the bedrock were thick enough to cause burial reheating. We demonstrate that burial associated with thick volcanic formations should be taken into account when interpreting thermochronological data from the WC or in similar volcanic-arc settings.